Antibacterial and efflux pump inhibitors of thymol and carvacrol against food-borne pathogens. (October 2016) - Miladi, Hanene; Zmantar, Tarek; Chaabouni, Yassine; Fedhila, Kais; Bakhrouf, Amina; Mahdouani, Kacem; Chaieb, Kamel
Abstract: In this study thymol (THY) and carvacrol (CAR), two monoterpenic phenol produced by various aromatic plants, was tested for their antibacterial and efflux pump inhibitors potencies against a panel of clinical and foodborne pathogenes. Our results demonstrated a substantial susceptibility of the tested bacteria toward THY and CAR. Especially, THY displayed a strong inhibitory activity (MIC's values ranged from 32 to 64 μg/mL) against the majority of the tested strains compared to CAR. Moreover, a significant reduction in MIC's of TET and benzalkonium chloride (QAC) were noticed when tested in combinations with THY and CAR. Their synergic effect was more significant in the case of THY which resulted a reduction of MIC's values of TET (2–8 fold) and QAC (2–8 fold). We noted also that THY and CAR inhibited the ethidium bromide (EtBr) cell efflux in a concentration-dependent manner. The rate of EtBr accumulation in food-borne pathogen was enhanced with THY and CAR (0, 250 and 500 μg/mL). The lowest concentration causing 50% of EtBr efflux inhibition (IC 50) was noticed in Salmonella enteritidis (1129) at 150 μg/mL of THY and 190 μg/mL of CAR respectively. These findings indicate that THY and CAR may serve as potential sources of efflux pump inhibitor in food-borne pathogens. Highlights: The emergence of multidrug-resistant and disinfectant resistant bacteria has increased. Thymol and carvacrol displayed an antimicrobial activity against food-borne pathogens. Thymol and carvacrol may modulate the susceptibility of resistant bacteria. They may considered as natural products with antibiotic resistance-modifying activity.